Metal–polymer nano-composite films with ordered vertically aligned metal cylinders for sub-wavelength imaging - Wu, Linda Yong Ling (2016)
We propose a self-assembled and anisotropically metal loaded large area PS-b-P4VP diblock copolymer film as a medium with hyperbolic dispersion for application in superlensing and nanolithography. We obtained domain sizes from 30 to 100 nm with successful demonstration of metal loading inside the nano-templates. The separation between the individual nanorods and their radius was effectively controlled by varying the molecular weights and compositions of the polymers. We apply Maxwell–Garnett homogenization and FDTD simulations to show the sub-wavelength imaging and lithography potential of these hyperbolic metamaterials (HMMs). A proof of principle nanolithography result demonstrates sub-wavelength imaging and lithography using the proposed HMMs.